Are aberrant phase transitions a driver of cellular aging?. (24th August 2016) - Alberti, Simon; Hyman, Anthony A.
Abstract : Why do cells age? Recent advances show that the cytoplasm is organized into many membrane‐less compartments via a process known as phase separation, which ensures spatiotemporal control over diffusion‐limited biochemical reactions. Although phase separation is a powerful mechanism to organize biochemical reactions, it comes with the trade‐off that it is extremely sensitive to changes in physical‐chemical parameters, such as protein concentration, pH, or cellular energy levels. Here, we highlight recent findings showing that age‐related neurodegenerative diseases are linked to aberrant phase transitions in neurons. We discuss how these aberrant phase transitions could be tied to a failure to maintain physiological physical‐chemical conditions. We generalize this idea to suggest that the process of cellular aging involves a progressive loss of the organization of phase‐separated compartments in the cytoplasm. Abstract : Phase transitions are emerging as a new mechanism of intracellular organization. Here, we hypothesize that age‐related fluctuations in physical‐chemical parameters trigger aberrant phase transitions with a consequent loss of control over intracellular organization. Our concept may explain many hallmarks of aging and the increasing risk of disease with age.